The Implementation Of Crossword Puzzle Game As Teaching Material To Develop Students’ Vocabulary In Grade X Of Ma. Mambaul Ulum Bata-Bata - Hafidurrahman, Moh.; Dannur, Moh.; Hakim, Abdul; Amin, Moh. (Lingua : Journal of Linguistics and Language, 2023)
Teaching English language cannot be separated from a good lesson plans that contain in syllabus and curriculum. Based on national curriculum, the aims of English in our country is “students can master four skills (reading, writing listening, vocabulary)”.  Some of the interesting method in teaching is game. To create interesting learning, teacher must have innovative technique, for exampel with crossword puzzle model on vocabulary material in grade X of MA Mambaul Ulum Bata-Bata . The first, teacher appreciates and provides motivation either by telling about the greatness of someone who is successful. The design of this research is classroom action research, since the research deals with crossword puzzle game to develop students’ vocabulary. The researcher uses classroom action research that used two cycles. The main characteristic of action research was the spiral activity consisting of planning, acting/implementing, observing, and reflecting. The result of the observation sheet showed that at the first meeting in cycle 1, most of the students still did not know what to do, and began the conversation well. It was still 36% students were active. At the second meeting of cycle 1, the involvement of the students was increasing to 55%. The result of the observation sheet in the cycle 2 showed that at the first meeting, most of the students began practiced actively and began study well, they looked very enthusiastic with this. It was 64% students were active. At the second meeting, the involvement of the students was increasing to 70%.